Anti‐PrP monoclonal antibody as a novel treatment for neurogenesis in mouse model of Alzheimer's disease. Issue 11 (21st October 2021) - Li, Ruolin; Ren, Ming; Yu, Yingxin
Abstract: Background: Alzheimer's disease (AD) is the most common degenerative disease characterized by cognitive impairment, memory decline, and language disorder for which there is no effective treatment. Neurogenesis has been indicated in AD and may play an important role in the pathogenesis of AD. Targeting this pathway is a new idea for the treatment of the disease. A recent study reveals that the cellular prion protein (PrP), a receptor for Aβ oligomers, regulates neurogenesis, and its elevated expression is related to cell differentiation. The aim of the present study was to investigate the neuroprotective effects of 6D11 (PrP monoclonal antibody) via neurogenesis promotion in APP/PS1 transgenic mice and Aβ‐induced cell model of AD. Methods: In the present study, 9‐month‐old male APP/PS1 mice were injected with 6D11. Then, the Morris water maze was used to examine the spatial learning and memory abilities of the mice in both groups, and immunostained was used to assess the level of Aβ, neurogenesis, and neural stem cells (NSCs) differentiation. Results: 6D11 attenuated cognitive deficits in APP/PS1 transgenic mice, which was accompanied by a decrease of the deposition of Aβ. In addition, 6D11 treatment promoted differentiation of the existing hippocampal cells to neurons. Conclusions: Our findings confirmed that 6D11 has a therapeutic effect in APP/PS1 transgenic AD mouse model and Aβ‐induced AD cell model, and the effect exerted via increase of neurogenesis and cell differentiation by transduction of Aβ peptide signal.